How do you solve the following system using substitution?: -3x + 3y= 3, -5x + y = 13

1 Answer
Oct 26, 2015

x=-3
y=-2

Explanation:

First, isolate y in the first equation.

color(blue)([1])" "-3x+3y=3

color(blue)([2])" "3y=3+3x

color(blue)([3])" "y=1+x

Now substitute the value of y in the first equation to y in the second equation.

color(red)([1])" "-5x+color(blue)(y)=13

color(red)([2])" "-5x+color(blue)((1+x))=13

color(red)([3])" "-4x=12

color(red)([4])" "x=-3

Now that we have the value of x, we will simply substitute this to the first equation.

color(blue)([4])" "y=1+(-3)

color(blue)([5])" "y=-2